การเตรียมความพร้อมครูนักเรียนทุนรัฐบาลก่อนเริ่มปฏิบัติหน้าที่ครูของประเทศไทย - แย้มกสิกร มนตรี; จิระโร พงศ์เทพ; โพธิ์ทอง วิลาวัลย์ (Journal of Research and Curriculum Development, 2016)
การวิจัยนี้มีวัตถุประสงค์เพื่อพัฒนาหลักสูตรเตรียมความพร้อมครูนักเรียนทุนรัฐบาลด้วยหลักสูตรที่สร้างขึ้น และประเมินผลการพัฒนาความพร้อมของครูนักเรียนทุนรัฐบาล กระบวนการพัฒนาหลักสูตรใช้กรอบแนวคิดของ Taba and Tyler กลุ่มตัวอย่างที่เก็บข้อมูลเพื่อนำมาเป็นสิ่งกำหนดหลักสูตรเป็นครูนักเรียนทุนรัฐบาลที่ผ่านประสบการณ์เตรียมความพร้อมมาก่อน และมีประสบการณ์จากการปฏิบัติหน้าที่ครูในโรงเรียนไม่น้อยกว่า 2 ปี หลักสูตรผ่านการสนทนากลุ่มผู้เชี่ยวชาญ และนำไปปฏิบัติการใช้กับครูนักเรียนทุนรัฐบาล รุ่นปี พ.ศ. 2556 ผลการประเมินการพัฒนาความพร้อมของครูนักเรียนทุนรัฐบาล พบว่า ครูนักเรียนทุนรัฐบาลมีความพึงพอใจต่อการได้รับการเตรียมความพร้อมก่อนปฏิบัติหน้าที่ระดับมาก ข้อค้นพบที่สำคัญสะท้อนว่า ภารกิจของครูที่ต้องปฏิบัติงานในโรงเรียนไม่สอดคล้อกับมวลประสบการณ์ที่สถาบันผลิตครูจัดให้กับนิสิตนักศึกษาครูแม้ว่าหลักสูตรที่พัฒนาเพื่อเตรียมความพร้อมครูนักเรียนทุนรัฐบาลจะพยายามจัดประสบการณ์เสริมเติมในส่วนที่ครูนักเรียนทุนรัฐบาลจะต้องปฏิบัติงานในโรงเรียนก็ยังไม่เพียงพอ และในงานวิจัยชิ้นนี้ มีข้อเสนอเชิงนโยบายต่อรัฐบาลเพื่อนำไปพิจารณากำหนดเป็นนโยบายต่อไปด้วย Preparation of Student-Teacher Recipients of the Thai Government Scholarship Prior to their Start of Duty The research aimed to develop the preparation for readiness curriculum,implement the designed curriculum, and evaluate the outcome of such development ofreadiness. The research employed Taba and Tylerûs process of curriculum development.The samples who yielded the data for curriculum details were experienced studentteacherswho participated in previous readiness preparation trainings with at least twoyears of working as school teachers. The curriculum underwent the expert focus groupdiscussion and was implemented with student-teacher recipients of the governmentscholarships of the year 2013. The results were highly satisfied with this preparation forreadiness prior to the start of their official duty. One important finding reflected that theteachersû assignments in school were not consistent with the massive experience of theteacher production institutes which had provided for the student-teachers. Althoughthe developed curriculum for readiness preparation was an attempt to supplementthe missing experience for these student-teachers, it was found to be insufficient.In addition, this research study concluded with several policy recommendations for thegovernment to consider.